Sea water thermo-saline characteristics off the Romanian coast and their influences on sprott (sprattus sprattus) shoaling in 1980 - Nae, Ion; Cociașu, Adriana; Butoi, Ilie (Cercetări Marine - Recherches Marines, 2026)
The present work is a first attempt to relating sprott shoaling to a couple of most important environmental factors - temperature and salinity off the Romanian coast of the Black Sea, in order to improve the knowledge of the factors influencing the life of the sprott and conditioning their exploitable shoalings mainly.